On the occurrence of Bérem dolerites dyke swarms (north east adamawa plateau, Cameroon) - Ngougoure Mouansie, Samira; Nkouandou, Oumarou Faarouk; Ganwa, Alaxendre Alambert; Fagny Mefire, Aminatou; Lise Carole, Atouba; Haman, Adama; Dinamou, Appolinaire (International Journal of Advanced Geosciences, 2022)
Petrography and geochemical outline studied carried out on Bérem dolerites have shown that they crosscut the local granitoıds of the basement toward N100-120, EW and N160E directions. Individual dyke may have 5 m to 50 m wide and extend along strike on 200 m to 3 km. Microscopic observations have distinguished the lavas of doleritic textures of ophitic to sub ophitic types. ICP-AES and ICP-MS geochemical analyses of representative samples have distinguished the lavas of basaltic trachyandesite of normative quartz-hypersthene compositions. All lavas belong to the same lavas series of continental tholeiites affinity which have undergone the fluids circulation and crustal contamination processes. Mantle of Bérem dolerites should be E-MORB mantle component which have experienced the relatively high partial melting rate. Bérem dolerites should be considered as imprints of late Pan African relaxation phase which cracks should have been filled by dolerite lavas.